Pengelolaan Kelas Dalam Pembelajaran Jarak Jauh: Tantangan dan Solusi Bagi Guru dan Peserta Didik - Mustikaati, Wina; Walidain, Abdah Birrul; Insari, Indah Putri; Syifa, Miana; Robiah, Siti (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Technological developments and the impact of the COVID-19 pandemic have accelerated the adoption of distance learning (PJJ) at various levels of education. However, the implementation of PJJ presents challenges in classroom management, such as limited interaction, low learning motivation, and technical barriers. This article aims to identify challenges and formulate strategic and applicable solutions in the management of PJJ classes. The research was conducted through a literature study with a qualitative descriptive approach. The results of the study show that PJJ classroom management requires technological skills, adaptive pedagogical approaches, effective communication, and collaboration between teachers, students, and parents. Strategies such as the use of digital media, active learning, and humanist and empathic approaches are the keys to success. With the implementation of these strategies, PJJ can create an inclusive and meaningful learning environment even though it is conducted online.